Hotspots and status of Fetal Alpha-Thalassemia from 2009 to 2023: a bibliometric analysis - Li, Qiuying; Li, Xinyan; He, Sheng; Li, Jiao (Frontiers in Pediatrics, 2024)
Objective: to evaluate the research status and development hotspots of fetal α-thalassemia by quantitatively analyzing the diagnostic status, key areas, related management measures and prospects of the disease by bibliometrics.: The global literature on fetal α-thalassemia and severe α-thalassemia from 2009 to 2023 in the WedWeb of Science Core Collection (WOSCC) was visually analyzed by VOSviewer and CiteSpace. Results: (1)The examination of the quantity of publications concerning fetal α-thalassemia indicates a rising tendency prior to 2018, followed by a decrease after 2018. (2)The United States, China, Italy, Thailand have published more papers, and the United States has more collaborating countries such as Italy and China. (3)Chiang Mai University and Harvard University are the top two institutions with the highest contribution. However, Chiang Mai University's H index (12) and citation frequency per article (8.05) are relatively low and the NC (6,342), H index (33) and citations per article (75.42) of Harvard University are higher than those of the other institutions. (4)Tongsong T, Gambari R and Fucharoen S are the top three prolific authors. Fucharoen S emerges as the most frequently cited author with 738 citations, excluding self-citations. (5)HEMOGLOBIN leading with 87 published papers